El predator ataca! = Predator attack! - Kenah, Katharine; Kenah, Katharine (Columbus, OH : Waterbird Books, 2005)
An introductory look at predators, animals that catch and eat other living things.
"3, confident reader"--Cover.
"English Spanish dual language."
Translation of: El predator ataca!
Text in English and Spanish.
Keywords: Animal attacks; Predatory animals; Bilingual books -- Spanish-English.